Role of serum S100B protein and NSE concentration in the diagnosis, and prognosis of patients with acute cerebral infarction - Hanh, Hoang Trong; Khanh, Hoang; Loi, Nguyen Cuu; Anh, Le Thi Phuong; Hung, Bui Manh; Hieu, Pham Trung; Nguyen, Tran Thua; Phuong, Le Thi Dieu (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
None.